Menguanya Aspirasi Goodgovernance di Desa: Pelajaran dari Protes Pilkades - Muh Syahbudin Latief (Magister Ilmu Administrasi Publik, 2010)
This article examines protests to village head election from a good government perspective. The villagers embarked on protests because of suspicion that elections were fraudulent. On one hand the protests can be seen as the struggle toward village democratization. To that end, the spread of protests is a reflection of the strong participation of village in the village political process. Protests can also be seen as the awakening of villager’s courage against the authoritarian and repressive government. However, it must be regarded as means of strengthening the aspiration of village people who demand village government to appreciate good governance values, which among other include transparency, accountability, responsibility, and participation. Dialectically, implementation of god governance values is prerequisite for innovation, creativity, and expression on one hand, and a source of encouragement for the configuration of democratization in the government, on the other.